Patient dumping, outlier payments, and optimal healthcare payment policy under asymmetric information - Tsuyoshi Takahara (Health Economics Review, 2016)
We analyze a rationale for official authorization of patient dumping in the prospective payment policy framework. We show that when the insurer designs the healthcare payment policy to let hospitals dump high-cost patients, there is a trade-off between the disutility of dumped patients (changes in hospitals' rent extraction due to low-severity patients) and the shift in the level of cost reduction efforts for high-severity patients. We also clarify the welfare-improving conditions by allowing hospitals to dump high-severity patients. Finally, we show that if the efficiency of the cost reduction efforts varies extensively and the healthcare payment cost is substantial, or if there are many private hospitals, the patient dumping policy can improve social welfare in a wider environment.
Keywords: I13; I18; L51; 330; Patient dumping; Healthcare payment policy; Adverse selection